Stabilizing Polymer–Lithium Interface in a Rechargeable Solid Battery. (14th November 2019) - Yan, Min; Liang, Jia‐Yan; Zuo, Tong‐Tong; Yin, Ya‐Xia; Xin, Sen; Tan, Shuang‐Jie; Guo, Yu‐Guo; Wan, Li‐Jun
Abstract: Solid polymer electrolytes (SPEs) are promising candidates for developing high‐energy‐density Li metal batteries due to their flexible processability. However, the low mechanical strength as well as the inferior interfacial regulation of ions between SPEs and Li metal anode limit the suppress ion of Li dendrites and destabilize the Li anode. To meet these challenges, interfacial engineering aiming to homogenize the distribution of Li + /electron accompanied with enhanced mechanical strength by Mg3 N2 layer decorating polyethylene oxide is demonstrated. The intermediary Mg3 N2 in situ transforms to a mixed ion/electron conducting interlayer consisting of a fast ionic conductor Li3 N and a benign electronic conductor Mg metal, which can buffer the Li + concentration gradient and level the nonuniform electric current distribution during cycling, as demonstrated by a COMSOL Multiphysics simulation. These characteristics endow the solid full cell with a dendrite‐free Li anode and enhanced cycling stability and kinetics. The innovative interface design will accelerate the commercial application of high‐energy‐density solid batteries. Abstract : An in situ formed mixed ion/electron conducting interlayer formed from an intermediary Mg3 N2 layer decorated on polyethylene oxide is designed. The as‐synthesized electrolyte manipulates ion and electron distributions on the surface of the Li anode, endowing the solid full cell with a dendrite‐free Li anode and enhanced cycling stability and kinetics.